Ribosomal Protein S3 Gene Silencing Protects Against Cigarette Smoke-Induced Acute Lung Injury - Jinrui Dong; Wupeng Liao; Hong Yong Peh; W.S. Daniel Tan; Shuo Zhou; W.S. Fred Wong (Elsevier, 2018)
Chronic obstructive pulmonary disease (COPD) is estimated to be the third leading cause of death by 2030. Transcription factor NF-κB may play a critical role in COPD pathogenesis. Ribosomal protein S3 (RPS3), a 40S ribosomal protein essential for executing protein translation, has recently been found to interact with the NF-κB p65 subunit and promote p65 DNA-binding activity. We sought to study whether RPS3 gene silencing could protect against cigarette-smoke (CS)-induced acute lung injury in a mouse model. Effects of an intratracheal RPS3 siRNA in CS-induced lung injury were determined by measuring bronchoalveolar lavage (BAL) fluid cell counts, levels of inflammatory and oxidative damage markers, and NF-κB translocation. Lung RPS3 level was found to be upregulated for the first time with CS exposure, and RPS3 siRNA blocked CS-induced neutrophil counts in BAL fluid. RPS3 siRNA suppressed CS-induced lung inflammatory mediator and oxidative damage marker levels, as well as nuclear p65 accumulation and transcriptional activation. RPS3 siRNA was able to disrupt CS extract (CSE)-induced NF-κB activation in an NF-κB reporter gene assay. We report for the first time that RPS3 gene silencing ameliorated CS-induced acute lung injury, probably via interruption of the NF-κB activity, postulating that RPS3 is a novel therapeutic target for COPD. Keywords: ribosomal protein S3, chronic obstructive pulmonary disease, NF-KB, siRNA, cigarette smoke